Branding dan Kelanggengan Merek: Studi pada Public Relations Kusuma Sahid Prince Hotel Solo - Anita Ratna Sari; Eny Susilowati (Academic Journal of Da'wa and Communication, 2021)
The management of Kusuma Sahid Prince Hotel as one of heritage hotels has its own challenges to attract customer interest in the midst of competition for a number of hotels in Solo, one of which is about branding. This study aims to describe the branding of "The Truly Heritage Hotel" through the Public Relations (PR) of Kusuma Sahid Prince Hotel Solo in maintaining the brand longevity. The research method used was descriptive qualitative with the theory of Brand Expression and Brand Communication. The data collection was carried out through observation, interview, and documentation. In order to test the validity of the data, this research used the source triangulation technique and the interactive data analysis. The results showed that Kusuma Sahid Prince Hotel Solo implemented several strategies, in the form of: brand positioning, brand identity, brand personality, sales promotion, event, public relation, direct marketing, company sponsorship, and advertising. Besides, in order to maintain the brand longevity, the branding process was linked to brand origin and ownership, brand architecture, brand scope, and brand size. Furthermore, Kusuma Sahid Prince Hotel Solo had the brand characteristics used to maintain the brand longevity as "The Truly Heritage Hotel".